A Study on the Bagrid Catfish (Chrysichthys nigrodigitatus) from Itapaji Water Reservoir, Ekiti State, Nigeria - Tomiwa , A. Akindele; Omotayo , Fagbuaro; Marry , A. Adegbola; Folasade , A. Ola-Oladimeji; Olugbemi , V. Ekundare (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
The Silver catfish, Chrysichthys nigrodigitatus is a highly valued food fish included among the dominant commercial catches exploited in major rivers of Africa. To obtain biological data for management and to contribute to their ecological knowledge some aspects of biology were studied on 120 samples of C. nigrodigitatus collected from Itapaji dam reservoir in Ekiti State, Nigeria between the months of June 2021 to September 2021. The specimens were transported to Zoology and Environmental Biology Post-graduate laboratory of Ekiti State University, where they were examined, relevant data recorded and analysed. The data was analysed using MS excel 2010, PAST and IBM SPSS Statistics 22. Results obtained from the male and female in the same population showed significant differences (P < 0.05) in 19 of these morphometric features. The males had a mean standard length of 21.36cm (21.20 to 34.8 cm) while the mean standard length in females was 18.52cm (20.50 to 29.40cm). The mean condition (K) values were 0.90, 0.98 and 0.94 for males, females and sexes combined respectively indicating that they are indeed in good condition. The gonado-somatic index (GSI) peaks in June for both sexes. Hepatosomatic index (HSI) was higher in females than in males. The sex ratio of 1M: 1.5F was in favour of females. The ingested food items of C. nigrodigitatus were evaluated by occurrence and numerical abundance methods in which algae and diatoms are dominant. The mean weight of the internal organs for male was (10.15g) and for female it was (11.65g). The histopathology studies show they are in good condition. Absolute (individual) fecundity of the fish ranged from 2500 eggs (TL of 19.5cm and body weight of 90g) to 6500 eggs (TL of 27.3cm and body weight of 246g) Mean fecundity ranged between 1857 and 4652eggs. Hence this study provides useful information for culturing and improvement of this fish species.